Hinduism, Ecological Conservation, and Public Health: What Are the Health Hazards for Religious Tourists at Hindu Temples? - Michal Apollo; Yana Wengel; Heike Schänzel; Ghazali Musa (Religions, 2020)
This exploratory ethnographic study aims to understand the visitation experience and to identify health hazards at pilgrimage sites in India. Specifically, this research aims to assess the tourism potential of holy Hindu temple sites located along well-known pilgrimage routes. During our fieldwork, we visited several of the most significant Hindu temples in India. Framed by a critical ethnography lens, our study used unstructured interviews with local stakeholders, as well as observations and reflexive notes. The findings revealed that most of the temples have serious safety, hygiene, accessibility, and environmental issues. A lack of action could lead to serious consequences for locals and tourists. For example, important for tourism, warnings of pandemics have been sounded over the years, and disease pandemics originating in India may only be a matter of time. We propose some immediate solutions and areas for future research.